Macroeconomic effects of tax changes: Evidence from a sample of OECD countries - Georgios Karras (SPOUDAI - Journal of Economics and Business, 2019)
This paper investigates the macroeconomic effects of tax changes. Using annual data from 1870 to 2013 for a panel of seventeen OECD economies, the empirical findings show that changes in the tax rate have temporary effects on the real growth rate but permanent effects on the level of output. The tax multiplier is estimated at -0.25 for the first year and around -0.60 in the long run. The evidence shows that tax changes have much stronger effects on investment than on consumption, and that they exert only short -term influence on the interest rate. An increase in the tax rate appears to raise the price level permanently and the inflation rate temporarily, implying stronger aggregate-supply than aggregate-demand effects.
Keywords: E32; E62; H20; 330; Taxes; Economic Growth; Tax multiplier